Communicable Diseases Intelligence volume 10 issue 18 - 8 September 1986 - whole issue - No author listed (Communicable Diseases Intelligence, 1986)
Whole-issue pdf, comprising: Virus Reporting Scheme Articles Cholera outbreak: Indonesia Cholera - Health advice for the Australian international traveller Malaria acquired with double chemical prophylaxis: chloroquine plus fansidar (R) - [Canada] AIDS surveillance - Australia Prevention of perinatal Hepatitis B - [USA] Amodiaquine-induced hepatitis [France] Hepatitis B associated with jet injections in California [USA] Spread of Hepatitis B by adopted children in Sweden Notice to readers Revised 'Notifiable Diseases Australia - 1985". The revised figures for the period 1 January to 31 December 1986 previously published in CDI 86/11 are included in this Issue on page 14. Australia - Communicable Diseases Intelligence Reporting Period 19/08/1986 - 01/09/1986 Notifiable Diseases reported in Australia - 1985 - revised figures 1 January 1985 to 31 December 1985